Verapamil and Collagen-Induced Platelet Reactions- Evidence for a Role for Intracellular Calcium in Platelet Activation - Han, P; Boatwright, C; Ardlie, N G (Thrombosis and Haemostasis, 1983)
Calcium is considered to have an essential role in various platelet reactions. Using platelets preincubated with Chlortetracycline, a fluorescent divalent cation indicator, and suspended in a calcium free medium, it was shown that collagen-induced intracellular calcium redistribution occurred before the platelet shape change, the release reaction and thromboxane B2 formation. Verapamil, at concentrations which affect intracellular calcium movements, inhibited intracellular calcium redistribution in platelets and the subsequent collagen-induced platelet reactions. Low concentrations of the ionophore A23187 overcame the inhibitory effect of verapamil. These experiments provide evidence that intracellular calcium mobilization is involved in the activation of platelets by collagen. Furthermore, calcium may be released from different cellular pools since platelet secretion, aggregation and thromboxane B2 formation were inhibited at lower concentrations of verapamil than was the platelet shape change.
Keywords: Platelet activation; Collagen; Verapamil; A23187; Chlortetracycline; Calcium mobilization